2016
DOI: 10.1109/tmtt.2016.2609409
|View full text |Cite
|
Sign up to set email alerts
|

Spatial In-Body Channel Characterization Using an Accurate UWB Phantom

Abstract: Abstract-Ultra-wideband (UWB) systems have emerged as a possible solution for future wireless in-body communications. However, in-body channel characterization is complex. Animal experimentation is usually restricted. Furthermore, software simulations can be expensive and imply a high computational cost. Synthetic chemical solutions, known as phantoms, can be used to solve this issue. However, achieving a reliable UWB phantom can be challenging since UWB systems use a large bandwidth and the relative permittiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Regarding the correlation in transmission -calculated to study the diversity of the UWB in-body channel in several locations of transmitting antennas-it decreases rapidly whatever the distance between transmitter antennas was, as authors concluded in [134], in an IB2IB phantom-based setup. They also concluded that correlation is quite high when transmitting antennas are aligned at the same height and the distance between their centers is below 5 cm for the IB2OB scenario.…”
Section: Correlationmentioning
confidence: 92%
See 3 more Smart Citations
“…Regarding the correlation in transmission -calculated to study the diversity of the UWB in-body channel in several locations of transmitting antennas-it decreases rapidly whatever the distance between transmitter antennas was, as authors concluded in [134], in an IB2IB phantom-based setup. They also concluded that correlation is quite high when transmitting antennas are aligned at the same height and the distance between their centers is below 5 cm for the IB2OB scenario.…”
Section: Correlationmentioning
confidence: 92%
“…Therefore, more studies to enhance the communication among implanted sensor networks should be conducted. On the other hand, the path loss is fitted by a log-distance model for the IB2OB scenario, as concluded in [134]. Likewise, the shadowing is well-fitted by a normal distribution.…”
Section: B Uwb Radio Channel Performancementioning
confidence: 97%
See 2 more Smart Citations
“…To this end, it is necessary to develop accurate tissue phantoms, which are materials that imitates the electromagnetic characteristics of human tissues. They are cost-effective and easy to produce, allowing the assessment of different electromagnetic parameters related to transmission [1] and correlation [2] for wireless implanted devices in Body Area Networks (BAN), as well as specific absorption rate [3] and dosimetry in mobile communications scenarios. Electromagnetic tissue phantoms avoid as well the experimentation with animal specimens and humans in in vivo conditions [4] in preliminary stages.…”
Section: Introductionmentioning
confidence: 99%